Formulation and Evaluation of Extended-Release Bilayer Tablets Containing Empagliflozin and Metformin Hydrochloride for Diabetes Mellitus Management (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This study systematically evaluates the formulation development of bilayer tablets combining Empagliflozin and Metformin hydrochloride for diabetes mellitus management. The formulation design encompassed drug-excipient compatibility, flow characteristics, and the development of immediate and extended-release layers. Differential Scanning Calorimetry (DSC) confirmed compatibility between Empagliflozin, Metformin hydrochloride, and selected excipients (HPMC and Avicel), showing no significant variations in onset and peak melting points after 4 weeks of incubation. Flow properties were assessed and demonstrating excellent flow characteristics suitable for tablet formulation. Both pre and post- compression analysis were found to be within pharmacopoeial limits. In an attempt to define the best formulation parameters, a concept known as Central Composite Design (CCD) as well as Full Factorial Design (FD) were used. CCD experiments pointed to the strong impact of Hydroxypropyl cellulose and Croscarmellose content on the tableting properties. It was useful while employing the FD method in conducting a comprehensive evaluation of several factors affecting Empagliflozin formulation to accomplish optimization. This detailed investigation underscores the importance of systematic assessments in formulating bilayer tablets with Empagliflozin and Metformin hydrochloride, ensuring stability, efficacy, and compliance, ultimately contributing to advancements in drug delivery systems and improved patient outcomes.